Hubungan Kondisi Lingkungan Dengan Keberadaan Telur Nyamuk Aedes di Wilayah Kerja Puskesmas Bontokassi Kabupaten Takalar - Rasjid, Ashari; Ahmad, Hamsir; Hermawan, Harman (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
The mosquitoes Aedes aegypti and Aedes albopictus are vectors of dangue hemorrhagie fever, having unique habitat and behavior characteristics. The Aedes aegypti and Aedes albopictus mosquitoes can generally be found in settlements, people’s homes and buildings. One of the ways can be used to determine the existence of Aedes aegypti mosquitoes in one district is conducting a survey and installing an ovitrap.The study aims to know the relationship between temperature, humidity, lighting conditions and environmental cleanliness with the density of Aedes mosquito eggs in Bontokassi Public Health Center, Galesong Selatan District, Takalar Regency. This type of this research is Analytical Observational with a cross-sectional study design. The results show that the presence of Aedes mosquito eggs in the working area of the bontokassi public health center has an average of 67,3% inside the house and 55,8% outside the house. There is no relationship between indoor air temperatures and outdoor air temperature, is no relationship air humidity, there is a relationship lighting conditions, and there is a relationship between the cleanliness of the outside environment and the existence of Aedes mosquito eggs Bontokassi Public Health Center. In a conclusion, There are 3 categories of variables which have no relationship and 4 variable category which has a relationship with the density of Aedes mosquito eggs in Bontokassi Public Health Center. The researcher suggested for all community to keep the home environment clean.  Keywords : Aedes aegepty; Ovitrap, Dengue Fever